2021
DOI: 10.21037/tlcr-20-1123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prognostic factors in surgically treated oligometastatic non-small cell lung cancer: a systematic review

Abstract: Background: Since the concept of oligometastatic (OM) disease was introduced in the oncological scenario of non-small cell lung cancer (NSCLC), these patients progressively became a new category of stage IV NSCLC in whom the multimodality approach, including surgery, may improve prognosis. This systematic review aimed to investigate the clinical prognostic factors in OM-NSCLC surgically treated with radical intent.Methods: This systematic review is reported following the Preferred Reporting Items for Systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
0
2
Order By: Relevance
“…In the meta-analysis of Ashworth et al, adenocarcinoma histology was associated with an improved OS [ 13 ]. However, this association was not supported by other retrospective studies and systematic reviews [ 15 , 62 ]. In a systematic review by Bertolaccini et al, a histologic grading of G1/G2 was found to be a positive prognostic factor for OS [ 62 ].…”
Section: Patient Selection Criteria For Local Aggressive Therapycontrasting
confidence: 62%
See 1 more Smart Citation
“…In the meta-analysis of Ashworth et al, adenocarcinoma histology was associated with an improved OS [ 13 ]. However, this association was not supported by other retrospective studies and systematic reviews [ 15 , 62 ]. In a systematic review by Bertolaccini et al, a histologic grading of G1/G2 was found to be a positive prognostic factor for OS [ 62 ].…”
Section: Patient Selection Criteria For Local Aggressive Therapycontrasting
confidence: 62%
“…However, this association was not supported by other retrospective studies and systematic reviews [ 15 , 62 ]. In a systematic review by Bertolaccini et al, a histologic grading of G1/G2 was found to be a positive prognostic factor for OS [ 62 ]. While the molecular mechanisms and the effect of the tumor microenvironment on cancer progression and metastasization have been extensively investigated in model systems, translational studies evaluating the real impact of the tumor microenvironment on treatment success in oligometastatic disease are lacking [ 61 ].…”
Section: Patient Selection Criteria For Local Aggressive Therapycontrasting
confidence: 62%